Novel Employer-Oriented Frameworks to Manage Delay Causes in Traditional (Non-BIM) and Building Information Modelling (BIM)-Enabled Construction Projects - Barqawi, Mohammad Tawfiq (Curtin University, 2024)
Construction delays are considered among the foremost common issues that inflict adverse effects on project owners and employers. Thus, it is essential to identify the causes of delays to attenuate and reduce the delays and related expenses. No prior research has addressed employer delays separately in a detailed manner from the more comprehensive coverage of countries or continents. A few studies on delays consider traditional and building information modelling (BIM) current practices for different continents. Hence, this research aimed to develop a novel and comprehensive framework to address or prevent construction delays caused by employers.